Effect of delivery method on thyroid hormone levels at birth, a cross-sectional study - Ava Nemati; Mahrokh Dolatian; Samira Behboudi-Gandevani; Malihe Nasiri; Maryam Tohidi (Mashhad University of Medical Sciences, 2020)
Introduction: The effects of labor pain and hypoxia during delivery on the neonatal metabolic and endocrinological profile after birth, especially thyroid function hormones, are unknown. This study was performed with aim to determine the relationship between delivery method with thyroid function hormone levels and blood gases in the newborn cord at birth. Methods: This cross-sectional study was performed on 240 singleton and term pregnant women with no history of thyroid problems in Shahid Akbarabadi Hospital in Tehran, Iran, in 2018-2019. Subjects were divided into three groups of 80 cases based on mode of delivery: natural delivery, emergency cesarean delivery and elective cesarean delivery. Immediately after birth, thyroid stimulating hormone (TSH), triiodothyronine (T3) and thyroxine (T4) and also blood gases including umbilical vein oxygen pressure (PO2), carbon dioxide pressure (PCO2), oxygen saturation (O2saturation) and pH of neonates' cord were measured and their relationship with mode of delivery was evaluated. Data were analyzed by SPSS software (version 20) and variance analysis test, covariance analysis, Kruskal Wallis, and Tukey Test. PResults: Mean TSH level in emergency cesarean section group was higher than normal delivery group (P = 0.001) and also higher than selective cesarean section group (P = 0.034). Mean of TSH level was significantly different between normal delivery and elective cesarean section (P = 0.001). Mean of pH and PO2 was higher in selective cesarean section group than normal delivery (p=0.024, p=0.001) and was also higher than emergency cesarean section group (P = 0.014, p=0.037). Also, mean serum level of cord PCO2 was significantly different between three groups (p=0.1) and was significantly lower in selective cesarean section group than other two groups (p=.001).Mean serum level of cord PCO2 was not significantly different between normal delivery group and selective cesarean group (p>0.05). Conclusion: The present study showed that labor pain and hypoxia during delivery may increase TSH levels.